Correlation between maxillary sinus floor topography and relative root position of posterior teeth using Orthopantomograph and Digital Volumetric Tomography - Kalkur, Chaithra; Sattur, Atul P; Guttal, Kruthika S; Naikmasur, Venkatesh G; Burde, Krishna (Asian Journal of Medical Sciences, 2017)
Background: Maxillary sinus and its close proximity to the oral cavity make it a common clinical concern for medical and dental practitioners. Due to anatomical complexities, it is difficult to evaluate the relation between the root apices of maxillary posterior teeth and the floor of maxillary sinus which is essential for diagnosis of sinus pathology, understanding the path of dental infection and planning of dental treatment. Aims and Objectives: To correlate the topographic relationship of the maxillary sinus floor to the maxillary posterior teeth roots as imaged by pairs of Orthopantomograph (OPG) and Digital Volumetric Tomography images (DVT). Materials and Methods: A total of 510 maxillary teeth from 85 patients were classified according to their topographic relationship to the maxillary sinus and measured according to their projection lengths on the sinus cavity using OPG and DVT modalities. Results: In cases of classification 0, 85% and in classification 1 , 55.3% cases shows similar classification in both OPG and DVT. 28.5% of cases in both imaging modalities show classification 2. Only 15.9% of teeth roots exhibits classification 3. 11.1% of cases showed classification 4.The panoramic radiograph showed a statistically significant 2.24 times longer root projection on the sinus cavity in OPG comparison to DVT images. Conclusion: Teeth roots projecting in to the sinus in OPG, shows no vertical protrusion in to the sinus in DVT images. Hence DVT was better than OPG with measurements that were more exact and closer to anatomical reality. Asian Journal of Medical Sciences Vol.8(1) 2017 26-31